2005
DOI: 10.1211/0022357055768
|View full text |Cite
|
Sign up to set email alerts
|

Selective β1-adrenoreceptor blocking activity of newly synthesized acyl amino-substituted aryloxypropanolamine derivatives, DPJ 955 and DPJ 890, in rats

Abstract: The in-vivo beta-adrenoreceptor antagonistic activity of test compounds DPJ 955 and DPJ 890 was assessed against beta-adrenoreceptor agonist (isoprenaline) induced tachycardia in anaesthetized rats. The selectivity to block isoprenaline responses on different &beta-adrenoreceptor subtypes (beta(1), beta(2) and beta(3)) of the test compounds was carried out on isolated rat right atria, isolated rat uterus and isolated rat colon preparations, respectively. Intravenous injection of isoprenaline alone in anaesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…This is confirmed by the observation that the estimate for affinity in vivo based on total drug (K B ¼ 7.0 nM; 95% confidence interval 3.1-15.4 nM) is different from the in vitro affinity (K B ¼ 1.9 AE 0.48 nM). [31][32][33][34] The findings in the current study are, thus, in agreement with previous studies. Moreover the conclusions are consistent with our previous work on basis of a mechanism-based PKPD model a series of beta-blockers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is confirmed by the observation that the estimate for affinity in vivo based on total drug (K B ¼ 7.0 nM; 95% confidence interval 3.1-15.4 nM) is different from the in vitro affinity (K B ¼ 1.9 AE 0.48 nM). [31][32][33][34] The findings in the current study are, thus, in agreement with previous studies. Moreover the conclusions are consistent with our previous work on basis of a mechanism-based PKPD model a series of beta-blockers.…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, free drug concentrations are considered the best predictor of drug effect for S (−)‐propranolol. This is confirmed by the observation that the estimate for affinity in vivo based on total drug ( K B = 7.0 nM; 95% confidence interval 3.1–15.4 nM) is different from the in vitro affinity ( K B = 1.9 ± 0.48 nM) 31–34. The findings in the current study are, thus, in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, unique estimates of the K B (affinity) have been obtained that are independent of the administered dose of atenolol. Finally, the obtained estimates of the in vivo K B of atenolol are close to the values obtained in in vitro bioassays (Nandakumar et al, 2005). These findings confirm that in vivo homeostatic feedback mechanisms play a minor role in the estimation of these pharmacodynamic parameters.…”
Section: Discussionsupporting
confidence: 83%
“…Although ␤ 1 -, ␤ 2 -, and ␤ 3 -adrenoceptor are present in mammalian heart, the positive chronotropic effects of isoprenaline in vivo are caused by ␤ 1 -adrenoceptors (Wellstein et al, 1987;Piercy, 1988;Nandakumar et al, 2005). It is occasionally suggested that ␤ 2 -adrenoceptors are involved in the effect on heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…The tachycardia produced by isoprenaline is primarily due to β ‐adrenoceptor activity in the heart ( Chiu et al ., 2000 ). Although β 1 , β 2 and β 3 adrenoceptora are present in mammalian heart, the positive chronotropic effect of isoprenaline in vivo are brought about by β 1 ‐adrenoceptors ( Wellstein et al ., 1987 ; Piercy, 1988 ; Nandakumar et al ., 2005 ). It is occasionally suggested that β 2 ‐adrenoceptors are also involved in the effect on heart rate, however only a small population of functional β 2 ‐adrenoceptors is present in the heart of WKY rats ( Doggrell and Surman, 1994 ).…”
Section: Discussionmentioning
confidence: 99%